Dialectics of Islam and Culture in Forming the Social Structure of the Rencong Telang Indigenous Community - Zainuddin, Mahli; Sudarman, Sudarman; Salim, Luthfi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
This research discusses the dialectics of Islam and culture in the syara mangato adat mamakai tradition in forming the social structure of the Rencong Telang community in Kerinci Jambi. The existence of the culture of Rencong Telang Indigenous People is increasingly disappearing with the arrival of the Synchretic Islamic and Puritan Islamic civilizations. This research employed qualitative research with a phenomenological approach and multiple cases. Data was collected through documentary research, secondary data collection, participant observation, in-depth interviews, and focus group discussions (FGD). The results of the research find that the tradition of syara mangato adat mamakai shows the dialectics of Islam and culture in forming the social structure of the Rencong Telang indigenous community. In this case, Islam is one of the sources of applicable norms and customary law. The social life of the Rencong Telang community is regulated through traditional institutions which are manifested in the formulation of four customs and four laws. The four customs contain traditional principles. Meanwhile, Law Four is in the form of technical and applied regulations.